The financial sustainability of robot-assisted surgery (RAS) - Tinka, Domonkos; Lukacs, Eszter (Transformations In Business & Economics, 2026)
In a previous study, it was concluded that the da Vinci robotic systems installed in the Hungarian healthcare system were, with one privately funded exception, fully financed by EU funds. The present article drives a similar conclusion on a global scale. Massive public investments, or reimbursements, are needed to ensure the prevalence and financial sustainability of robotic surgical systems. The financial sustainability of RAS depends on the economic development of a country and its healthcare system, the number of medical schools, the history of robotic surgery and the funding mechanisms of the healthcare system. Even in the most advanced economies of the world, access to the benefits of RAS may be burdened by limitations in terms of financial (funding) and geographical access.